Assessment of Frequency and Severity of ADRS Related with CHOP Therapy in Lymphoma Treatment - Jameela Jamali, Abdullah Dayo, Naheed Memon, Ubed-Ur Rehman Mughal, Yasmeen Qureshi, Salman Ahmed Rajput, Shireen Bhurgari, Zeeshan Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Lymphoma a blood related cancer usually treated by using combination of various chemotherapeutic agents, one of the common treatments is CHOP (Cyclophosphamide, Doxorubicin, Vincristine, Prednisone). Objective: Objective of this study was to identify frequency and severity of ADRs affecting various systems due to CHOP therapy from which patients are suffering, so that proper health strategy can be designed to overcome them. Methodology: study conducted was a prospective, observational enrolled 100 patients suffering from Non-Hodgkin Lymphoma and receiving CHOP combination therapy from November 2015 to April 2018 at Cancer Hospital Jamshoro, sampling technique used was purposive. The response on ADRs was recorded and these were verified by comparing against British National Formulary (2017) ad Lexi Comp Drug Information Handbook (2015). Results: Among 100 patients enrolled aged 18-65 years in which females comprise the majority. The common ADRs reported were nausea 71%, fatigue 69% and alopecia 68% The patients who responded about high severity ADRs also tend to stay longer as compared to those with less severity one. Conclusion: The study results show that patients receiving lymphoma treatment suffers from high severity ADRs require supportive medical care as this lead to prolong effects after dose cycle. These patients must be counselled for supportive medication and food intake to prevent additional health risks to achieve maximum therapeutic benefits. Keywords: Cancer, Anticancer Drugs, Chemotherapy, CHOP Therapy, ADRs